Survey: secure opportunistic routing protocols in wireless networks. (8th November 2019) - Saidi, Hanane; Gretete, Driss; Adnane, Addaim
Opportunistic routing (OR) protocols in wireless network schemes are a rich research field. These protocols select the best path in order to send information and take the broadcasting medium into consideration. OR tends to reach better reliability and performance than traditional routing (TR). However, they are both equally vulnerable to the same attacks because wireless networks might be deployed in hostile or unwatched environments. The approaches in terms of routing are mainly focusing on energy preservation, robustness, etc. However few work has been done to secure routing protocols especially in OR. In this paper, we are going to give an analysis of OR protocols their classifications as well as an overview on the security approaches available for opportunistic routing protocols.